The Moral Value and Characteristics of the Main Character in Skyscraper by Rawson Marshall - Tiana, Delis Meta; Rahayuningsih, Retno; Wibowo, Ary Iswanto; Sasmita, Octaria Arni (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2024)
This research aims to show the moral values and characteristics of the main character in Rawson Marshall Thurber's Skyscraper movie. The study employed the descriptive qualitative methodology. The data analysis method utilized a new criticism analysis, which includes analyzing the structure of theme, the structure of feel/feelings, the structure of tone and atmosphere, and the structure of mandate. The research object under study covers the entire duration of the movie. The researchers concluded that:1) The packaging of moral values ​​in Skyscraper movie by Rawson Marshall Thurber has three moral values ​​that help build the character of the main character. 2) The main character in this movie is portrayed as persistent, honest, and courageous. 3) The observations indicate that the main character's characteristics are influenced by moral values, highlighting the significance of moral principles in overcoming challenges and emphasizing that a positive mindset leads to optimism, perseverance, and a good attitude.